Reducing risks of human exposure to antimicrobial resistance originating from livestock supply chains - Roskam, J.L.; Gocsik, E.; Lansink, A.O.; Schut, Marc; Saatkamp, H.W. (2021)
Antimicrobial resistance is one of the biggest health threats for both humans and animals. This justifies the need for a conceptual framework that provides an integrated assessment of the measures and strategies that can be applied within livestock supply chains to reduce the risks of human exposure to resistant pathogens. The aim of this study is therefore to provide a comprehensive supply chain-based conceptualisation that describes the main measures and strategies to Rev. Sci. Tech. Off. Int. Epiz., 39 (3) 2 2/26 reduce the risks of human exposure to resistant pathogens. The conceptual framework presented in this study makes a distinction between on-farm and beyond-farm decision-making contexts. The on-farm decision-making context focuses on the strategies that can reduce antimicrobial use. The beyond-farm decision-making context focuses on the prevalence of (pathogenic) microorganisms. The focus of this framework is on Western European food production systems. A panel consisting of Dutch policy makers on antimicrobial issues assessed various aspects of the framework, including correctness, completeness and consistency. It is concluded that the conceptual framework provides a sound theoretical basis for economic decision-support for policy makers to reduce the risks of human exposure to resistant pathogens originating from livestock supply chains.